Engineered barrier systems (EBS) in the Safety Case: Design confirmation and Demonstration : Workshop Proceedings Tokyo, Japan 12-15 September 2006 - Organisation for Economic Co-operation and Development (Paris : OECD, 2007)
These proceedings present the main findings from, and the papers delivered at, the fourth NEA-EC workshop on Engineered Barrier Systems (EBS), which took place in Tokyo, Japan, in September 2006. This final workshop of the series focused on strategies and methods to demonstrate that EBS designs will fulfill the relevant requirements for long-term safety, engineering feasibility and quality assurance. The workshop highlighted that large-scale experiments have confirmed the feasibility of techniques for manufacturing and installing engineered components in disposal systems and have also provided valuable lessons to improve designs and refine practical aspects to construct and implement EBS. --Publisher's description.
Introduction -- Workshop objectives and structure -- Working group findings
'NEA No. 6257.'
Keywords: Radioactive waste disposal in the ground -- Congresses; Radioactive waste sites -- Design and construction -- Congresses; Radioactive waste sites -- Evaluation -- Congresses